Evidence for mitochondrial heteroplasmy in the freshwater bug Aphelocheirus aestivalis (Fabricius, 1794) (Insecta: Heteroptera): a challenge for future studies based on mtDNA markers - Agnieszka Kaczmarczyk-Ziemba; Dariusz Halabowski; Gavril M. Berchi; Tomasz Rewicz; Pál Boda; Tomasz Krepski; Giedrė Višinskienė; Desislava Stoianova; Grzegorz Tończyk; Adrianna Momotko; Julia Chylińska; Michael J. Raupach (Hydrobiologia, 2025)
The mitochondrial genome of Metazoa is predominantly maternally inherited, providing a valuable genetic marker in various fields such as phylogenetics and phylogeography. However, mitochondrial heteroplasmy, where multiple copies of mitochondrial DNA (mtDNA) coexist within an individual or even cell, presents a challenge to the use of mtDNA markers. This phenomenon may arise from replication errors, mutagenic processes, or paternal leakage. In this study, we investigated mitochondrial heteroplasmy in the freshwater bug Aphelocheirus aestivalis (Fabricius, 1794) using both Sanger and Illumina sequencing approaches. Our analyses confirmed the presence of diverse mtDNA variants within individual specimens collected from various locations across Europe. Signals of mitochondrial heteroplasmy were observed in chromatograms derived from both female and male individuals, indicating a prevalent phenomenon across A. aestivalis populations in general. Further comparative analyses of COI (partial cytochrome c oxidase subunit I) haplotypes indicated their high similarity and complex phylogenetic relationships. In turn, Illumina sequencing of a single male specimen revealed 102 heteroplasmic sites across the protein-coding sequences of mitogenome. Our results suggest the widespread and heritable nature of mitochondrial heteroplasmy in A. aestivalis , highlighting its importance for future phylogenetic and phylogeographic studies.